Hubungan Pelaksanaan Pendidikan dan Pelatihan Terhadap Produktivitas Kerja Karyawan Pada Hotel di Bogor - Melati, Berti Anggun (Ikatan Da'i Indonesia, 2022)
The purpose of this research is to discuss and analyze the training program and its effect on work productivity. The analytical method used in this research is descriptive quantitative analysis, with multiple linear regression analysis, validity test and reliability test. The results of hypothesis testing have proven that there is a significant effect between the implementation of the training program on employee productivity. Tests prove that the implementation of training has a positive effect on employee productivity by R 0.73% while the remaining 27% is not in this study which includes employee willingness to train, report employee progress and increase knowledge. While the most dominant variables affect employee productivity at hotels in Bogor. are training, awarding and different educational backgrounds.